2019
DOI: 10.1038/s41598-019-45330-9
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Meta-analysis of Magnetic Stimulation Therapy for Urinary Incontinence

Abstract: Magnetic stimulation (MS) is a novel approach for treating urinary incontinence (UI), but its applicability remains unclear. This systematic review and meta-analysis were conducted to evaluate the effects of MS treatment on UI. A literature search was performed in EMBASE, PubMed and Cochrane Library (from May 2018 to August 2018), and all randomized control trials (RCTs) published in English were screened to determine whether they met the inclusion criteria. A manual search of the reference lists of the retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…Although the European Association of Urology (EAU) 2018 guidelines, based on evidence from 2007 and 2008 (two papers), do not recommend the use of MS in adult women with SUI (level of evidence: 2a), it however omits an important study conducted recently, which will be presented below. MS is a noninvasive, passive method of stimulating the roots of the sacral nerves or PFMs [104]. The MS method uses a special chair with a therapeutic head placed in the seat; as the magnetic field can penetrate through clothes, stimulation can be carried out in clothing, which significantly increases the comfort of therapy [105].…”
Section: Magnetic Stimulationmentioning
confidence: 99%
“…Although the European Association of Urology (EAU) 2018 guidelines, based on evidence from 2007 and 2008 (two papers), do not recommend the use of MS in adult women with SUI (level of evidence: 2a), it however omits an important study conducted recently, which will be presented below. MS is a noninvasive, passive method of stimulating the roots of the sacral nerves or PFMs [104]. The MS method uses a special chair with a therapeutic head placed in the seat; as the magnetic field can penetrate through clothes, stimulation can be carried out in clothing, which significantly increases the comfort of therapy [105].…”
Section: Magnetic Stimulationmentioning
confidence: 99%
“…Based on our review of articles, there are different designs, such as PFMT alone or in combination with the strengthening of synergistic muscles or electrical stimulation. But our results showed that ES is another common and essential modality for subjects with SUI [7].…”
Section: Modern Rehabilitationmentioning
confidence: 50%
“…According to our review, a few articles are about PFMT, electrical stimulation, and whole-body vibration as a novel treatment, but the available literature proves that PFMT and electrical stimulation are recommended as the first line of therapy in patients with Stress Urinary Incontinence (SUI). PFMT is a simple method, and it is recommended in patients with SUI [7,15]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are certain clinical trials on the employ of MS to ameliorate female SUI, and the results are positive. Two meta-analyses 22,23 and one systematic review 21 both mentioned the effect of MS on the treatment of SUI, but they had some deficiencies in the number of included RCTs, the analysis of outcome indicators, and the treatment mechanism of MS. In addition, if the only source of literature search is limited to the English could potentially miss a lot of researches.…”
Section: Introductionmentioning
confidence: 99%